Experimental Study on Cement and Fine Aggregate Replacement with Coal Bottom Ash in Seawater-Mixed Concrete - Md Noor, Nurazuwa; Irmawaty, R.; Rashid, Mohamad Amirul Qaiyum (International Journal of Integrated Engineering, 2022)
An experimental study was carried out to study the properties of concrete made with seawater as total mixing water, ground coal bottom ash as binary cement and coal bottom ash as sand replacement. The first stage mixes were prepared with three percentages (0, 10, 20 and 30) of ground coal bottom ash as partial replacement of binder. The second stage mixes involved 10 percent of ground coal bottom ash with 25%, 50%, 75% and 100% of coal bottom ash replacing natural sand. Properties investigated were materials properties, binder chemical composition, concrete hardened density, compressive strength, and SEM. Test on hardened density was conducted on 7 and 28 days. Ground coal bottom ash was identified as Class F, while coal bottom ash has low specific density and high-water absorption compared to natural sand. Concrete density and compressive strength decreased on use of coal bottom ash as fine aggregate. Compressive strength was seen to decrease as CBA percentage rose, with the maximum value being 44.4 MPa for combination of 10 percent ground coal bottom ash and 25 percent coal bottom ash. Series with 10% CBA (ground coal bottom ash) reduces by roughly 51% while maintaining a sufficient structural strength value. The findings of this investigation showed that it is possible to produce seawater-concrete, which incorporates coal ash in concrete.